Mapping High Level Thinking Abilities Using Solo Taxonomy in Class VIII Students in Middle Schools in Bandar Lampung City - Nukhbatul Bidayati Haka; Devi Wahyu Ningsing; Anisa Oktina Sari Pratama; Hardiyansyah Masya; Ismi Rakhmawati (Yayasan Darussalam Bengkulu, 2025)
Initial research indicates that students' higher-order thinking skills (HOTS) in biology remain low, primarily due to a lack of integration between science and everyday life, as well as the continued dominance of traditional teaching methods. This study aims to analyze students' higher-order thinking skills using SOLO taxonomy to gain deeper insights into their cognitive achievements in solving HOTS questions. The researcher employed a stratified random sampling technique. Four schools were selected to ensure the research sample represents the general characteristics of all schools in Bandar Lampung City. By choosing schools with diverse backgrounds, such as accreditation, geographical location, and learning support facilities, the study results can better reflect the actual conditions of the broader school population. Data were collected through interviews, documentation, and tests. This qualitative research utilized data analysis techniques, including data reduction, data presentation, and drawing conclusions based on the findings. The study results indicate that the average higher-order thinking skills of students in schools A, B, C, and D, based on SOLO taxonomy, are at the multistructural level at 41.37%, the relational level at 28.88%, and the extended abstract level at 28.75%. A total of 41.37% of students demonstrated medium-level higher-order thinking skills, while 57.63% fell into the high category. A key finding of this study is that the extended abstract indicator had the lowest average compared to other indicators. This is attributed to the more complex demands of the questions, which require students to evaluate, synthesize, and apply concepts in new contexts tasks they rarely encounter.